Treatment outcomes and clinical relevance in patients with double expressor DLBCL - Sirapat Rungwittayatiwat (2022)
Background: Double-expressor lymphoma (DEL) was found to account for 20- 30% of DLBCL. We conducted this study to analyze the survival, the clinical presentation, and the factors associated with treatment outcomes in DEL-DLBCL. Methods: A retrospective study of 291 patients diagnosed with DLBCL during January 2015 - December 2018 was conducted. Results: Of the 291 patients, the median age was 63 years, germinal center B cell-like DLBCL (GCB) and non-GCB subtypes were found in 32% and 68%, respectively. DEL was found in 46% of 264 patients with available immunohistochemistry staining for MYC protein. Patients with DEL was significantly more common in elderly patients (p= 0.017) and non-GCB subtype (p= 0.006). High serum lactate dehydrogenase (LDH) levels and high Ki-67 index were significantly found in DEL patients than non-DEL patients (p= 0.024 and p= 0.04, respectively). The 3y-OS rate was shorter in the DEL group than in the non-DEL group, 58.7% versus 78.9% (p=0.026), whereas no significant difference in 3y-DFS was identified between these groups (58.4% versus 67.7%, p= 0.343). Independent factors affecting OS and DFS in DEL patients were ECOG 3-4, high LDH levels, extranodal involvement> 1 site, high IPI, and stage III-IV in univariate analysis. Conclusions: High incidence of DEL was observed in this study, especially in patients aged 60 years or older and non-GCB subtype. Patients with DEL showed dismal DFS and OS.